2019
DOI: 10.46325/gabj.v3i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis on the morphometry of local goats breed in the western of Algeria

Abstract: The objective of this study is a morphometric characterization of local goats in western of Algeria. With the use of 19 quantitative variables, we carried out a discriminant analysis on 119 goats and 32 bucks divided into 4 Wilayas (Tlemcen, Adrar, Naama and Bechar). The discriminant analysis on males was not significant. As for the female population, the analysis of variance (ANOVA) on the region effect was highly significant p=1.32 x 10-11. A clear separation has been found between the populations, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Various studies have shown high genetic diversity in African indigenous goat populations [21][22][23][24]. With increased temperatures and recurring droughts resulting from climate change, especially in the Horn of Africa, livestock adaptation to the environment is critical in production.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown high genetic diversity in African indigenous goat populations [21][22][23][24]. With increased temperatures and recurring droughts resulting from climate change, especially in the Horn of Africa, livestock adaptation to the environment is critical in production.…”
Section: Discussionmentioning
confidence: 99%
“…In Algeria, the results of the study carried out by Kady et al,2013;Fantazi et al 2017;Belantar et al. 2018 andBelkhadem et al, 2019 intend to characterize goat farming in the mountainous regions of Kabylia on 94 breeders, confirm the extensive nature of the goat farming system in these regions, where it is noted that breeding and reproduction techniques are poorly mastered, in addition to the lack or absence of extension and structuring of the goat sector. In their comparative study of goat production systems in Andalusia and northern Morocco, (Benjelloun et al, 2015;Chentouf et al (2009) recorded semiextensive production systems based on grazing for half of the herd's needs.…”
Section: The Case Of North Africamentioning
confidence: 93%
“…Goat farming in Algeria is one of the most widespread agricultural activities in harsh regions. It allows their pastoral resources to be transformed into quality products; goat milk and goat meat are indeed interesting nutritional sources, but also contribute to the income of rural populations (Sahraouiet al, 2016;Fantaziet al, 2017;Belantaret al, 2018;Belkhadem et al, 2019).…”
Section: Introductionmentioning
confidence: 99%